La comunicación intrafamiliar y su incidencia en el desarrollo socio-afectivo de las niñas y niños del primer año de educación básica de la escuela 3 de Diciembre del cantón Paltas provincia de Loja, en el periodo 2012-2013 - Ponce Torres, Maritza Josefina (2015)
This research titled DOMESTIC COMMUNICATION AND ITS IMPACT ON SOCIO-EMOTIONAL DEVELOPMENT OF CHILDREN FIRST YEAR OF BASIC EDUCATION SCHOOL "DECEMBER 3" THE Paltas Canton province of Loja, 2012-2013 The overall objective was to: analyze the influence of family communication in the socio-emotional development of children from the first year of basic education School "of December 3" Avocados Canton Loja Province, 2012-2013. The methods used for the preparation of this research work were: scientific, inductive-deductive, analytical and descriptive statistical model that served them help to effectively achieve the proposed goal. The techniques and instruments used were: a survey, the same as it was aimed at the parents of the first year of Basic Education School "December 3" to determine the factors involved in domestic communication of children of the first year of basic education in the same, the teachers to verify the influence of family communication in the socio-emotional development children of the first year of basic education in the School "of December 3" Avocados Canton Loja province, 2012-2013 children and direct observation to verify the influence of family communication in the socio-emotional development the children of the first year of education of the School "December 3" Canton Paltas Loja province, 20012-2013 period. It analyzed the results of the survey of parents concludes: 43% have an unsatisfactory communication within their homes and 31% of communication is satisfactory and 26% very satisfactory. From the results of the survey of teachers is concluded that 100% said that if domestic media influences in the socio affective development of students. Direct observation made by children in a general analysis there is a low level of domestic communication therefore this affects the socio-emotional of the children.